Hubungan Kondisi Lingkungan Rumah dengan Keberadaan Jentik Ae.Aegypti - Tusy Triwahyuni; Ismalia Husna; Devita Febriani Putri; Miya Medina (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2020)
Background: Dengue hemorrhagic fever is a disease caused by serotype 1-4 viruses (DEN-1, DEN-2, DEN-3, DEN-4). The entry of the virus into the human body to cause symptoms has a period of 3-5 days. Goals: Knowing the relationship between home environment conditions and the existence of larva Ae.aegypti at puskesmas of way Kandis Bandar Lampung. Method: This study was conducted using a cross-sectional study design. The samples of this study were 100 samples. The sampling technique in this study is a total sampling. The instrument used was the observation sheet and questionnaire. The analyzed being used was the chi-square test. Result: The result of statistic analysis using Chi-square test suggest that the variables related to the larva Ae. Aegypti is puddle(P-value = 0,039; OR= 2,729). Unrelated variables include the ornamental plants, distances between homes, hanging clothes, wire netting. Conclusion: puddle is the variables in home environment conditions that related to larva Ae.aegypti in Way Kandis region. are the unrelated variable relationship between home environment conditions and the existence of larva ae.aegypti in region Way Kandis.